Rapid-deployment aortic valve replacement for severe aortic stenosis: 1-year outcomes in 150 patients. (23rd March 2017) - Theron, Alexis; Ravis, Eleonore; Grisoli, Dominique; Jaussaud, Nicolas; Morera, Pierre; Candolfi, Pascal; Boleckova, Jana; Lagier, David; Amanatiou, Cecile; Messous, Lyna; Gariboldi, Vlad; Collart, Frederic
Abstract: OBJECTIVES: This study aimed to evaluate the safety and effectiveness of rapid-deployment aortic valve replacement (RDAVR) for severe aortic stenosis (AS). METHODS: All consecutive patients with severe AS who underwent RDAVR with the EDWARDS INTUITY bioprosthesis were prospectively included in a single-centre, cohort study between July 2012 and April 2015. Clinical examination and transthoracic echocardiography were performed preoperatively and at 1-month and 1-year follow-up. RESULTS: We included 150 patients: mean age 76.8 ± 6.2 years, 68.7% male and mean EuroSCORE II 3.4 ± 3.7%. Implantation was successful in all: 103 (68.7%) had isolated aortic valve replacement (AVR) and 47 (31.3%) had concomitant procedures. For isolated AVR, mean cross-clamp and cardiopulmonary bypass times were 37.6 ± 13.3 and 59.9 ± 20.4 min, respectively. Overall, the 1-year Kaplan–Meier survival rate was 97.1% (95% confidence interval 92.4–98.9%). At 1 year, stroke occurred in 5 patients (3.34%), myocardial infarction in 1 (0.69%), endocarditis in 1 (0.69%), early explantation in 1 (0.67%), pacemaker implantation in 8 (5.6%) and Grade 2 periprosthetic regurgitation in 4 (3.2%; no grade 3 of 4). There were significant decreases from baseline ( P  < 0.001) in the proportion at New York Heart Association Class III/V (35.3–4.1%), mean gradient (54.9 ± 17.3 mmHg to 11.3 ± 4.8 mmHg) and mean left ventricular mass index (160.3 ± 44.8 g/m 2 to 118.5 ± 39.4 g/m 2 ). Mean indexed effective orifice area at 1 year was 1.02 ± 0.37 cm 2 /m 2 . Ten patients (6.6%) had severe patient–prosthesis mismatch. CONCLUSIONS: RDAVR for severe AS provided favourable outcomes over 1 year.